Assessing Competence in Medicine and Other Health Professions - Violato, Claudio; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This comprehensive, yet accessible, text demystifies the challenging area of competence assessement in medicine and the health sciences, providing a clear framework and the tools for anyone working or studying in this area. Written by a single, highly experienced, author, the content benefits from uniformity of style and is supported and enhanced by a range of pedagogic features including cases, questions and summaries. Essential reading for all students and practitioners of medical education, it will also be an invaluable guide for allied health professionals and psychologists with a general interest in assessment, evaluation and measurement and a useful library reference.
Foundations. Introduction. Competence in Medicine. Basic Statistics for Testing. Validity and Reliability. Validity I Logical and Content. Validity II Correlational Based and Between Group Differences. Validity III Advanced Methods. Reliability I. Reliability II. Test Construction and Evaluation. Formats of Testing for Cognition, Affect and Psychomotor Skills. Multiple Choice Items. Constructed Response Items. Measuring Clinical Skills with the Objective Structured Clinical Exams (OSCE) Checklists, Questionnaires, Rating Scales and Direct Observations. Evaluating a Test: Item Analyses. Methods of Setting Cutoff Scores (Pass / Fail) References. Glossary. Index of Terms. Index of Names. Appendices.
Includes bibliographical references and index.
Also available in print format.
Keywords: MEDICAL / Administration; Competency-based assessment; Fitness to practice; Healthcare assessment; Medical education; Medical evaluation; Clinical competence; Medical care -- Quality control; Electronic books